FORMULASI SEDIAAN GEL EKSTRAK DAUN SUKUN (Artocarpus altilis) SEBAGAI PENYEMBUHAN LUKA BAKAR PADA KELINCI DENGAN VARIASI KONSENTRASI CARBOPOL 940 SEBAGAI GELLING AGENT - Putri Rinda Sari; Supriyadi Supriyadi; Inaratul Rizkhy Hanifah (As-Syifaa Jurnal Farmasi, 2021)
Breadfruit leaves are medicinal plants containing compounds such as flavonoids, saponins, tannins, polyphenols that function in wound healing. This study aimed to determine the variation of the concentration of the gelling agent carbopol 940 on the physical properties of the gel and the duration of the burn wound healing process on gel administration. This study used New Zealand White rabbits. They were divided into five groups. They were positive control (bioskin®), negative control, breadfruit leaf extract gel formula with variations in carbopol concentrations of 0,5%, 1%, and 2%, respectively. Burn percentage was analyzed using SPSS with Kolmogorov- Smirnov test to see normality, Levene test to see homogeneity, if the data is normally distributed and homogeneous, followed by Two Way ANOVA analysis with Post hoc Tukey significance of 0.005. The results of breadfruit leaf extract variations in the gelling agent carbopol 940 affect the physical properties. The increase in the concentration of the gelling agent causes an increase in viscosity, adhesion and decreases dispersion. Variations in the concentration of carbopol effective for healing burns was formula II (breadfruit leaf extract gel formula with variations in carbopol concentrations of 1%). Therefore, the provision of breadfruit leaf extract gel can accelerate the healing process of burns